The 6 types of working genius a better way to understand your gifts, your frustrations, and your team - Lencioni, Patrick (Dallas, TX Matt Holt Books, an imprint of BenBella Books, Inc, 2022)
New York Times bestselling author Patrick Lencioni provides a groundbreaking new model for finding joy in work, avoiding misery and frustration, getting more done, and working better with others. The 6 Types of Working Genius details a simple and lightning-fast way to discover and use your natural, God-given talents
Keywords: Teams in the workplace-Genius-Ability.